Structure-Based Identification of Natural MTH1 Inhibitors for Breast Cancer Therapy via Molecular Docking and Dynamics Simulations - Abdullah S. Alawam; Mubarak A. Alamri (Crystals, 2025)
Breast cancer is a prevalent malignancy worldwide. Human MutT homolog 1 (MTH1) is over expressed in breast tumors, and cancer cells rely on MTH1 for survival. This protein ensures the integrity of the nucleotide pool by preventing the integration of oxidized 2′-deoxynucleoside triphosphates (dNTPs) during DNA replication. Therefore, inhibiting MTH1 pharmacologically emerged as a valid target in treating breast cancer. In the present study, we screened biologically active phytochemicals from the NPACT database to discover potential inhibitors of MTH1. Molecular docking analysis was employed to identify the binding conformation and the interaction pattern. The top five compounds were selected for detailed analysis based on their superior binding affinity and interactions with crucial residues (Asn33, Gly36, Tyr7, Phe72, Trp117, Lys23, and Phe27, Glu100) of MTH1. Additionally, the ADMET profile of selected compounds highlighted the high intestinal absorption, low toxicity, and acceptable metabolic stability, exhibiting their potential as drug candidates. Furthermore, in silico validation of selected compounds was performed through molecular dynamics (MD) simulation, which revealed that the resultant complexes are appreciably stable. Compounds revealed RMSD values ranging between 1.0 and 1.5 Å, indicating strong and stable binding conformations. PCA analysis revealed restricted conformational sampling, highlighting stabilization, particularly with ZINC14727630, ZINC14819291, ZINC14781695, and ZINC95099417. MM-GBSA confirmed the stability of the ligand–protein complexes, with ZINC14819291, ZINC14727630, and ZINC95099417 demonstrating the most stable interactions with MTH1, with total binding free energies of −32.46, −45.06, and −33.44 kcal/mol, respectively. Our results support that these natural compounds could act as potential anti-MTH1 for ameliorating the breast cancer. However, experimental validation is required to validate the efficacy of these molecules and robustness of this anticancer approach.